Fundraising for development and alternative financing sources : address - Bourne, Compton ([CDB] [St. Michael]BB, 2009)
Looks at customary sources of development finance and sub-regional development banks. Discusses the implications of the current global crisis and the role of international financial institutions and multilateral development banks.